Electrolyte, method and device for metal surface treatment
By using dry electrolytes and coordination agents of sulfonic acid in metal polishing technology, ion transport technology is used to solve the shortcomings of mechanical wear and electropolishing systems, achieving more efficient metal surface polishing and longer equipment life.
Patent Information
- Application Number
- CN202411602997.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2019-02-21
- Filing Date
- 2019-11-06
- Publication Date
- 2025-01-07
AI Technical Summary
In the existing metal polishing technology, mechanical wear systems lead to uneven wear and surface pollution. The electropolishing system does not have enough effect on micron-level roughness smoothing, and is not suitable for some metals and alloys.
The metal surface is polished by ion transport using dry electrolyte containing sulfonic acid, and ion transport is carried out using porous particles and sulfonic acid in conductive liquid, combining complexing agents to improve metal ion transfer efficiency and surface smoothing effect.
A more uniform metal surface polishing is achieved, which reduces surface pollution and excessive rounding problems, improves polishing speed and effect, is suitable for a variety of metals and alloys, and extends the service life of dry electrolytes.
Smart Images

Figure BDA0005128790880000031 
Figure BDA0005128790880000032 
Figure BDA0005128790880000051
Abstract
Description
[0001] This application is a divisional application of the original Chinese invention patent application entitled "Use of sulfonic acid in dry electrolyte for polishing metal surface by ion transport", of which the application number of the original application is 201980051684.9, the application date of the original application is November 6, 2019, the PCT international application number is PCT / ES2019 / 070753, the international application date is November 6, 2019, and the date of entry of the PCT international application into the national phase is February 2, 2021. Technical Field
[0002] The field of the invention is that of industry focused on smoothing, buffing and polishing metal surfaces, with applications in fields such as, for example, the dental, medical, automotive and aerospace industries.
[0003] Purpose of the invention
[0004] The object of the present invention relates to a method for smoothing and polishing metal surfaces, characterized by the use of ion transport using a free solid body containing sulfonic acid as electrolyte and also using a free solid body containing sulfonic acid to perform the method. The use of a free solid body containing sulfonic acid has significant advantages and features that imply a significant novelty compared to the prior art.
[0005] Background of the Invention
[0006] There are stable systems for polishing metals, characterized by the use of particles not bound to any support, meaning free solid bodies that are mechanically worn away by friction due to the relative movement between the particles and the surface to be treated. The particles must be harder than the material to be treated.
[0007] Systems based on mechanical wear lack uniformity due to the fact that the effect of wear is related to the pressure between the surface and the particles. This means that protruding metal parts are subject to more wear than closed parts. This often leads to excessive rounding of the vertices and edges of the parts to be treated. This is a significant hindrance in the use of mechanical systems for metals that require precision or sharp edges.
[0008] In addition, systems based on mechanical wear produce deformations on the metal surface at a level that depends on the particle size. In the process, the metal surface is contaminated with inclusions from the particles. These modifications of the composition of the metal surface generally lead to a reduction in, for example, chemical resistance, tensile strength or durability.
[0009] There are also established systems for polishing metals, characterized by the use of an electric current on the metal immersed in a liquid electrolyte. These electropolishing systems provide a final metal surface that is free of foreign inclusions.
[0010] However, electropolishing systems have a smoothing effect on roughness in the micrometer range. Conventional commercial electropolishing systems typically require a roughness reduction in the range of 50% to 60% of the initial roughness. In many applications, this level of smoothing is not sufficient.
[0011] Furthermore, electropolishing systems tend to expose the crystalline structure beneath the metal or metal salt or metal oxide due to their inherent operation. This results in staggered surfaces, pores and other defects associated with the metal structure. Therefore, electropolishing systems are extended in metals and alloys that are inherently able to overcome these limitations due to their chemical properties, such as aluminum. However, they cannot be used in many other metals and alloys without these disadvantages.
[0012] Some problems of metal polishing systems based on mechanical wear and electropolishing systems are solved by the use of free solid bodies to polish metal surfaces by ion transport. The same applicant owns patent ES2604830A1, which relates to a "method for smoothing and polishing metals by ion transport with the aid of free solid bodies (...)". The free solid body can perform ion transport consisting of a set of porous particles retaining a given amount of liquid and a liquid conductive electrolyte retained in these particles (preferably ranging from 1% to 10% HF aqueous solution). However, the electrolyte does not provide satisfactory results in many metals (such as, for example, iron and iron alloys).
[0013] The object of the present invention is to develop an improved dry electrolyte for use in the process for smoothing and polishing metals by ion transport via free solid bodies. Summary of the invention
[0014] The use of sulfonic acids in free solid bodies or particles to polish metal surfaces by ion transport is novel in the art of metal polishing and has advantages and features explained below.
[0015] A dry electrolyte comprises a set of porous particles having the ability to retain a given amount of liquid and a given amount of conductive liquid.
[0016] The present invention specifically relates to a dry electrolyte comprising porous particles having the ability to retain a given amount of liquid and a given amount of a conductive liquid comprising at least one sulfonic acid.
[0017] In the present invention, the conductive liquid contains at least one sulfonic acid. The sulfonic acid is composed of the general formula RSO3H, where R can be any organic substituent, either alkyl or aromatic, another functional group or a halogen atom.
[0018] This is the general structure of sulfonic acids.
[0019]
[0020] Preferably, the sulfonic acid used is one that has a high solubility in water or another selected solvent. Also, preferably, those sulfonic acids that form soluble salts with the relevant metals. For example, but not for the purpose of limitation, sulfonic acids such as the following may be used: methanesulfonic acid CH3SO3H, trifluorosulfonic acid CF3SO3H, fluorosulfonic acid FSO3H, chlorosulfonic acid Cl S O3H, p-toluenesulfonic acid 4-CH3C6H4SO3H and aminosulfonic acid NH2SO3H, all of which are hereinafter referred to as
[0021]
[0022] The sulfonic acid can be used neat, either in liquid form at the operating temperature or in solution. The optimum concentration of the sulfonic acid should be determined empirically, since it depends on the chosen sulfonic acid, the solvent and also on the parameters of the component to be treated, such as the type of metal, the overall surface and the shape. In solution, the preferred choice of solvent is water or a polar solvent for reasons of conductivity and solubility. Preferably, water is the chosen solvent. Concentrations of sulfonic acid in the conductive liquid from 1% to 70% have proven to be active in this process. Preferably, the concentration is from 2% to 40%. These concentrations relate to the final concentration of the conductive liquid in the dry electrolyte, regardless of how the dry electrolyte is prepared.
[0023] Sulfonic acids are strong acids and their handling in liquids or solutions (as far as their use in classical electropolishing is concerned) carries with it a number of handling risks. In the liquid state or in solution, these sulfonic acids can produce undesirable corrosion on metal surfaces. Therefore, after the use of sulfonic acids in classical electropolishing, a further neutralization step is usually required.
[0024] However, when confined to porous particles, handling becomes easier and the risk of unwanted attack on the surface is prevented. Furthermore, due to the fact of being confined in the particles, the effect will be concentrated on the surface roughness peaks and therefore has a stronger effect when the effect is needed. Furthermore, the relative movement of the particles with respect to the metal part makes the particle-metal contact time relatively short, which facilitates a localized effect on the surface.
[0025] Sulfonic acids with organic waste (such as, for example, but not for the purpose of limitation, methanesulfonic acid, trifluorosulfonic acid, and p-toluenesulfonic acid) are much less polar than inorganic acids. Therefore, the reduced local polarity of these sulfonic acids facilitates their migration through non-polar resins. That is, the smaller sulfonic acid containing organic waste, methanesulfonic acid, will benefit from this effect while not maintaining steric hindrance.
[0026] In addition, other compounds can be added to the conductive liquid as complexing agents. These agents can capture the metal ions formed and increase the ability to remove metal oxides and salts from the surface.
[0027] Complexing agents with more than one functional group are called chelating agents. The effect of capturing and transferring metal ions is even higher through the use of chelating agents such as citric acid, EDTA or phosphonates. Due to the metal ions formed on the surface, the agent will have a high affinity and will help to carry the ions to the particles.
[0028] In a preferred embodiment, the complexing chelating agent is a polyether.
[0029] A polyether is defined as a compound comprising more than one ether group (COC) in its structure, without prejudice to the fact that it may in turn comprise other functional groups, such as ester, acid, amino, amide, and the like.
[0030] It has been examined that the addition of a polyether to the formulation of the liquid contained in the particles increases the speed of the transfer of ionic metals and therefore increases the speed of the polishing process.
[0031] In an even more preferred embodiment, the polyether is a linear alkyl polyether. Within the group of polyethers, crown ethers and alkyl polyethers are particularly included. The alkyl polyethers can have different shapes, such as linear, star, branched or comb. For the electropolishing process, we have found that linear alkyl polyethers provide the best results in this method because they are more active at the moment of forming a complex with the metal.
[0032] Within the class of linear alkyl polyether chelating agents, polyethylene glycol or PE is prominent, also known as poly(oxy-1,2-ethynyl), poly(ethylene oxide), polyoxyethylene, poly(ethylene oxide) and brand names such as Carbowax or Macrogol;
[0033] Within the class of linear alkyl polyether chelating complexing agents, polypropylene glycol or PPG is also prominent.
[0034] PEG and PPG are then represented, where R can be any group or functional group, preferably H or CH3. The number of repeating repeat units "n" is an important factor. Metal complexes with polyethers mostly adopt tetrahedral or octahedral conformations, which means that the metal ion is surrounded by four or six oxygen atoms, respectively, which is why the optimal number of repeats is around n=6, as it covers both possibilities.
[0035]
[0036] In the case of PEG, a molecular weight of 200 to 500 Da is preferred. Specifically, PEG 300 is most preferred.
[0037] Adding these polymers PEG and PPG to the conductive liquid used to prepare the dry electrolyte containing sulfonic acid, produces an electropolishing process at high speed and a unique final finish. This effect is definitely not obvious and is due to a series of cumulative factors: they are soluble in the phase where the sulfonic acid is found, they have the ability to form complexes with the removed metal ions, they act as phase transfer agents between the liquid retained in the particles and the gel phase of the particles themselves, they are stable to the intensity and voltage of the current subjected to the process, and, moreover, they are biologically safe.
[0038] The given amount of conductive liquid with which the porous particles are impregnated must be high enough to allow a measurable conductivity through the dry electrolyte. Furthermore, this amount must be below the saturation point of the porous particles so that there is no observable free liquid, thus a "dry" electrolyte. Preferably, the amount of conductive liquid is close to but below the saturation point of the porous particles. This amount must be determined empirically, as it depends on the sulfonic acid used, the type of resin, the temperature, the solubilizer, and the concentration. As an example, for AMBERLITE 252RFH, which has a water retention capacity of 52% to 58%, the optimal amount of conductive liquid consisting of 32% methanesulfonic acid in water ranges from 35% to 50%, relative to the absolute dry weight of the resin.
[0039] The material of the porous particles used is preferably based on a sulfonate polymer, which means that it has bound active sulfonic acid groups RSO3H or RSO3-. Preferably, the porous particle sulfonate polymer is based on a styrene copolymer and divinylbenzene. In particular, the porous particles can be an ion exchange resin such as, for example but without any purpose of limitation, AMBERLITE 252RFH, which has an ion exchange capacity of 1.7 eq / l, a density of 1.24 g / ml, a diameter ranging from 0.6 to 0.8 mm, and a water retention capacity ranging from 52% to 58%.
[0040] The synergistic effect between the sulfonic acid groups attached to polymers and the sulfonic acid in the conductive liquid is interesting. It has been found that, in an inconspicuous manner, the fact that these groups have the same chemical structure (although in different states) helps the circulation of metal ions from conductive liquids to polymer matrices. The direct chemical environment of metal ions in solution (by sulfonate coordination in solution) and in polymers (by sulfonate coordination attached to polymers) is similar. Therefore, the difference in energy levels between these states must be very low, which probably implies a transition state with low energy, which is converted into a higher speed liquid-solid transfer. This has two positive effects for the process, on the one hand, it makes the process more speedy, on the other hand, it improves the general ability of resins to act as metal ion receptors, which prolongs the useful life of dry electrolytes.
[0041] Thus, when sulfonic acids are used in dry electrolytes to polish metal surfaces by ion transport, the sum of these subtle and distinct effects allows for a faster process to achieve unique results while increasing the useful life of the dry electrolyte.
[0042] The present invention is also directed to a dry electrolyte comprising sulfonic acid.
[0043] Exemplary Embodiments
[0044] Hereinafter, some exemplary cases are presented without any limiting purpose.
[0045] Example 1
[0046] 1.5 kg of ion exchange resin AMBERLITE 252RFH was mixed with 550 ml of a 4% solution of methanesulfonic acid in water and homogenized to prepare a dry electrolyte. This dry electrolyte was used to polish a portion of an iron alloy having the following composition expressed in %: C (0.17-0.23), Si (0.40), Mn (0.65-0.95), V (0.025), S (0.050), Cr (0.35-0.70), Ni (0.40-0.70), Mo (0.15-0.55), Cu (0.35) Al (0.050), with a 5 cm 2 The counter electrode is a network of iridium on titanium. The current used is a positive wave of 50 Hz current at 20 V, which provides an intensity of 0.1 A. The part has a downward / upward movement at about 4 Hz and the dry electrolyte container is subjected to vibration. After 5 minutes of this process, the metal surface has acquired unique properties.
[0047] Example 2
[0048] A dry electrolyte was prepared by mixing 5.3 kg of ion exchange resin AMBERLITE 252RFH with 1950 ml of a 32% solution of methanesulfonic acid in water and homogenizing. This dry electrolyte was used to polish a portion of an iron alloy having the same composition as before, with a 36 cm 2 The counter electrode is a network of iridium on titanium. The current used is a positive wave of current at 50 Hz at 30 V. The part has an up / down movement at about 4 Hz and the dry electrolyte container is subjected to vibrations. After 10 minutes of this process, the metal surface has acquired unique properties.
[0049] Example 3
[0050] A solution was prepared using 550 mL of methanesulfonic acid 70%, 160 mL of PEG and 3000 mL of deionized water. The solution was mixed with 6.7 kg of ion exchange resin AMBERLITE 252 RFH and homogenized to prepare a dry electrolyte. The dry electrolyte was used to polish 36 cm 2 A part of carbon steel. The counter electrode used is a network of iridium on titanium. The current used is a positive wave of 50 Hz current at 30 V. The part has a downward / upward movement of about 4 Hz and the dry electrolyte container is subjected to vibration. After 5 minutes of this process, the metal surface has acquired unique properties.
[0051] With these descriptions it is expected that a person skilled in the art will be able to reproduce these results without any further problems.
Claims
1. An electrolyte for metal surface treatment, comprising: A plurality of free solid bodies having the ability to retain a quantity of liquid; a quantity of conductive liquid retained by the free solid body; as well as At least one sulfonic acid group is contained within the free solid body. 2 . The electrolyte according to claim 1 , wherein a sulfonic acid group is contained on the conductive liquid.
3. An electrolyte according to any one of the preceding claims, wherein the sulfonic groups are contained on a plurality of free solid bodies.
4. An electrolyte according to any one of the preceding claims, wherein the plurality of free solid bodies are porous particles.
5. An electrolyte according to any one of the preceding claims, wherein the plurality of free solid bodies are based on a sulfonate polymer.
6. An electrolyte according to any one of the preceding claims, wherein the plurality of free solid bodies comprises an ion exchange resin. 7 . The electrolyte according to claim 6 , wherein the included ion exchange resin has an ion exchange capacity of 1.7 eq / L.
8. The electrolyte according to claim 6 or 7, wherein the ion exchange resin has a density of 1.24 g / ml.
9. The electrolyte of claim 6, wherein the plurality of ion exchange resins have a diameter ranging from 0.6 to 0.8 mm.
10. An electrolyte according to any one of the preceding claims, wherein the concentration of sulphonic acid in the conductive liquid is between 1% and 70%.
11. An electrolyte according to claim 6 or 7, wherein the ion exchange resin is based on a styrene copolymer and divinylbenzene.
12. An electrolyte according to any one of the preceding claims, wherein the amount of conductive liquid retained by the solid body is an amount sufficiently high to allow measurable conductivity and below the saturation point so that no observable free liquid is present.
13. An electrolyte according to any one of the preceding claims, wherein the sulfonic acid comprises methanesulfonic acid.
14. An electrolyte according to any preceding claim, wherein the sulfonic acid groups comprise trifluorosulfonic acid.
15. The electrolyte of any preceding claim, wherein the second sulfonic acid group comprises fluorosulfonic acid.
16. The electrolyte of any preceding claim, wherein the second sulfonic acid group comprises chlorosulfonic acid.
17. An electrolyte according to any preceding claim, wherein the sulfonic acid groups comprise p-toluenesulfonic acid.
18. An electrolyte according to any preceding claim, wherein the sulfonic acid groups comprise aminosulfonic acid.
19. An electrolyte according to any preceding claim, wherein the conductive liquid comprises a complexing agent.
20. An electrolyte according to any preceding claim, wherein the complexing agent comprises a polyether.
21. An electrolyte according to any one of the preceding claims, wherein the polyether is a linear alkyl.
22. A method for surface treatment of a metal surface by ion transport, the method comprising: The metal surface is contacted with a plurality of dry electrolytes, each of the plurality of dry electrolytes comprising porous particles containing a conductive liquid in an amount below a saturation point of the porous particles, the porous particles comprising a sulfonate polymer comprising a first sulfonic acid group, the conductive liquid comprising a second sulfonic acid group soluble in the conductive liquid, the first sulfonic acid group and the second sulfonic acid group being in different states and having the same chemical structure.
23. A surface treatment device for treating a metal surface by ion transport, the surface treatment device comprising: A contact unit for contacting a metal surface with a plurality of dry electrolytes, each of the plurality of dry electrolytes comprising porous particles, the porous particles comprising a conductive liquid in an amount below a saturation point of the porous particles, the porous particles comprising a sulfonate polymer comprising a first sulfonic acid group, the conductive liquid comprising a second sulfonic acid group soluble in the conductive liquid, the first sulfonic acid group and the second sulfonic acid group being in different states and having the same chemical structure.